(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Ayurveda, a time-honored system of medicine, is known for its holistic approach, incorporating dietary and medicinal practices to treat various ailments. Among its many formulations, Shadang Paneeya stands out for its therapeutic potential in managing fever, excessive thirst, and related symptoms. Described in classical texts like the Charaka Samhita, this preparation consists of six herbs with unique pharmacological properties that have been explored for immune modulation, detoxification, and managing febrile conditions. Objective: This review critically evaluates the components and therapeutic significance of Shadang Paneeya, focusing on its relevance in contemporary medicine, particularly its immune-modulatory and therapeutic properties. Methodology: A comprehensive review of classical Ayurvedic texts and modern literature on the immunomodulatory, antiviral, and anti-inflammatory effects of the ingredients in Shadang Paneeya- including Musta (Cyperus rotundus), Parpatak (Fumaria parviflora), Usheera (Vetiveria zizanoides), Chandana (Santalum album), Uddichya (Pavonia odorata), and Nagar (Zingiber officinale)- was conducted. Discussion & Conclusion: The synergistic effects of these six ingredients support Shadang Paneeya’s role in treating fever, dehydration, and inflammation. However, more clinical studies are needed to confirm its safety and efficacy, establishing it as a valuable adjunct in modern healthcare, particularly for viral infections.